Walka o spadek po Mieszku III Starym (1202-1249) - Szempliński, Łukasz (My University, 2019)
Po śmierci Mieszka Starego doszło do walki o jego spadek. W pierwszej fazie walki przeciwko siebie stanęli Władysław Laskonogi i jego bratanek Władysław Odonic. Konflikt ten splótł się w spór kościelno-polityczny oraz spór pomiędzy stronnictwem juniorów i seniorów. Odonic należał do stronnictwa juniorów, związanego z arcybiskupem Henrykiem Kietliczem, natomiast Laskonogi do obozu seniorów. Pierwsza faza walki zakończyła się zwycięstwem Władysława Odonica, który w 1231 r. pokonał swego rywala. Większość rodów rycerskich poparła Laskonogiego, natomiast duchowieństwo było podzielone pomiędzy zwolennikami a przeciwnikami reformy. Druga faza konfliktu przebiegła pomiędzy Władysławem Odonicem i jego synami a śląską linią Piastów, której Laskonogi zapisał w testamencie Wielkopolskę. Pomimo początkowych sukcesów książąt śląskich, synowi Odonica w latach 1241-1249 wyszli z tej walki zwycięsko, jednocząc Wielkopolskę w swych rękach. Większość możnowładztwa oraz duchowieństwa poparła książąt wielkopolskich.

After the death of Mieszko the Old , there was a fight for his decline. In the first phase of the struggle against each other stood Władysław Spindleshanks and his nephew Władysław Odonic. This conflict was entwined in the church-political dispute between the party of juniors and seniors. Odonic belonged to the party of juniors, associated with Archbishop Henryk Kietlicz, and Spindleshanks to the opposition camp. The first phase of the fight ended with the victory of Władysław Odonic, who in 1231 defeated his rival. Most of the knight's families supported Spindleshanks, while the clergy were divided between supporters and opponents of the reform. The second phase of the conflict was between Władysław Odonic and his sons, and the Silesian Piast lineage, whom Spindleshanks wrote in the will of Greater Poland. Despite the initial successes of the Silesian princes, the sons of Odonic in the years 1241-1249 came out victorious, uniting Greater Poland in their hands. Most of the magnates and clergy supported the dukes of Greater Poland.
Struggle for inheritence from Mieszko III The Old (1202-1249)
Wydział Historyczny
Keywords: Spadek; reforma gregoriańska; Wielkopolska w XIII wieku; Władysław Odonic; możnowładztwo; Hereditary; gregorian reform; Greater Poland in XIII century; Wladyslaw Odonic; nobility